Postural performance while boxing with an opponent versus practice with a boxing bag - Cakmakci, O.; Erkmen, N.; Cakmakci, E.; Taskin, H.; Stoffregen, T. A. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2020)
Background. Boxing with an opponent may have a more important effects on postural control than hitting a punchbag. It might be vital for a boxer to know what happens to their body control after a slugfest. Problem and aim. We predicted that postural sway would be increased by fatigue after bouts under Bout and Bag conditions. Our other hypothesis was that sway in boxers after a bout would be higher after actual bouts than after a punchbag routine. Methods. Eleven active male boxers (age = 22.73 ± 4.15 years) volunteered to participate in the study. We measured the subjects` heart rate, blood lactate, and postural sway. We evaluated postural sway using the Biodex Balance System (BBS) on the dominant foot. Using a within-subjects design, each subject participated in two experimental conditions: Boxing with an opponent (Bout) and boxing with a punchbag (Bag). In each condition, we collected data six times: before boxing, after each round, and 10 and 20 minutes after boxing. Results. At Round 2, OSI scores were higher in the Bout condition than the Bag condition (t = 2.153; p = 0.044). For the Bout condition, the OSI scores in Round 1 and Round 2 were higher than in Pre-boxing (For Round 1, p = 0.031; for Round 2, p = 0.024) and in Recov-ery 20 (For Round 1, p = 0.044; for Round 2, p = 0.006). In the Bag condition, Recovery 20 had lower OSI score than Round 1 (p = 0.027).Conclusions. Our results suggest that competitive bouts impose greater challenges on postural control than working a punchbag, and that these differences are independent of general boxing-related fatigue.